2014
DOI: 10.1155/2014/621238
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Structure of Planktonic Microalgae Assemblages in Water Column Associated withPosidonia oceanica(L.) Bed in Tunisia

Abstract: Patterns of phytoplankton in areas with seagrass (Posidonia oceanica) and areas without seagrass were quantified in the coast of Chebba (East of Tunisia). Replicate samples were collected at August 2011, from four stations (separated by 500 of metres). The diversity of phytoplankton was high around P. oceanica meadows compared to area without seagrass. A possible explanation to this finding is that water motion and hydrodynamics forces cause leaves agitation allowing the passage of epiphytic species in the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…SIMPER generates a ranking of the species responsible for the significant differences. These analyses used a matrix composed of Bray-Curtis similarity coefficient generated with Log( + 1)-transformed species abundance data [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SIMPER generates a ranking of the species responsible for the significant differences. These analyses used a matrix composed of Bray-Curtis similarity coefficient generated with Log( + 1)-transformed species abundance data [13].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of variance (ANOVA) was used to test the hypothesis that the abundance of each group of taxa differed between disturbed and control stations [13]. Factor station was fixed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are particularly useful in this area with the recent establishment of several fish farms because epiphytic dinoflagellates are easily resuspended in the water column [8] and that abundance of phytoplankton in vegetated areas is higher than in the unvegetated station [16]. Moreover, Marr et al [60] concluded that the underestimation of toxic dinoflagellates associated with a toxic event may be due, in part, to the lack of sampling of the benthic and epiphytic communities.…”
Section: Journal Of Marine Biologymentioning
confidence: 99%
“…Epiphytic microalgae include many toxic species [13][14][15][16]. Knowledge of the epiphytes and potentially toxic species of microalgae is necessary to assess the influence of those species on fisheries exploitation and human health.…”
Section: Introductionmentioning
confidence: 99%